Community responses to environmental and livelihood impacts of government-initiated dumpsite in Tibar Village, Liquica District, Timor-Leste - Araujo, Ana Jeannie Alexandro de Corte-Real; Dizon, Josefina T.; Bawagan, Aleli B.; Rebancos, Carmelita M. (2015)
The study analyzed the community responses to environmental and livelihood impacts of government-initiated dumpsite in Tíbar Village, Liquíça District, Timor-Leste. A total of 82 household heads living in or adjacent to the dumpsite in Tíbar Village, Liquiça District, Tímor-Leste was identified through simple random sampling. Data were gathered through survey, ocular observation, key informant interview, focus group discussion, and review of secondary data. Frequency counts, percentages, means, standard deviations and ranges were used to describe the data generated from the household survey.
Majority of the respondents are married, head of families, males with mean age of 48 years, illiterate, with large households composed of five to ten members, and farmers earning about 100 USD per month.
They perceived that prior to the dumpsite operation, the soil, air, and drinking water were all good. However, after the dumpsite’s operation, the soil and air quality have been negatively affected. The respondents were not sure whether the leachate has affected the water source since no chemical test has been conducted to assess the quality of drinking water.
Almost all of the respondents said that there were technical, biophysical, and social problems caused by the operation of the dumpsite, but the government had no programs to address them. The respondents wanted community and government responses to address the negative impacts of the dumpsite on the environment and on their livelihood. These responses included scheduling of regular collection, provision of security services, payment initiatives, recycling initiatives, organizing waste pickers, waste segregation program, proper transportation system, collaboration and cooperation with non-government organizations and community-based organizations, and provision of alternative solution, among others. The only obvious response of the community members was the maintenance of cleanliness at the household level whereby they regularly cleaned their houses and the vicinities. However, they still lacked enough knowledge in reusing, recycling, and reducing wastes.
Keywords: Waste management and the environment; Open dumpsite; Community involvement